Uji Aktivitas Antibakteri Ekstrak Etanol Bunga Telang (Clitoria ternatea) pada bakteri Staphylococcus aureus dan Escherichia coli - Prasasti, Azmi; Fitria Lestari, Ima; Anggraini, Anita (NHM PRESS, 2024)
Butterfly pea flowers have benefits in almost all parts of the plant. One of the secondary metabolites in butterfly pea flowers functions as an antibacterial. This research aims to determine the ability of butterfly pea flower extract as an antibacterial against Staphylococcus aureus and Escherichia coli bacteria. The extraction method used was maceration with 70% ethanol solvent. The largest diameter of the inhibitory zone for S.aureus bacteria was found at a concentration of 90% butterfly pea flower extract of 20.8 mm. likewise for E.coli, the largest inhibitory zone diameter at a 90% concentration of butterfly pea flower extract was 15.4 mm